One size does not fit all: Lysosomes exist in biochemically and functionally distinct states. - Claudio Bussi; Maximiliano G Gutierrez (PLoS Biology)
Single-organelle resolution approaches have the potential to advance our knowledge of the heterogeneity of lysosome function. Challenging population-based models, we propose a "lysosome states" concept that links single lysosomes to function.